Dekonstruksi Konsep Moderasi Beragama Dalam Proses Pembelajaran - Romli Lie (Magister Pendidikan Agama Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This research is motivated by the fact that there are many cases of intolerance in the name of religion. Intolerant cases do not only involve adults but also involve teenagers and students as perpetrators and occur in schools. Education as a fundamental aspect is also one of the solutions to overcome this by providing an important religious moderation framework for managing religious life in a plural and multicultural Indonesian society. Religious moderation is an effort to mediate the existing diversity, both concerning ethnicity, religion, language, gender, race, social class, age, and so on, into something that has more potential and is easier in the context of learning and education. This research is library research. The purpose of the research is to comprehensively describe the concept of religious moderation in education and describe the implementation strategy of religious moderation in the learning process in classrooms. In analyzing the data, researchers used Jacques Derrida's deconstruction theory. The result of this study is that the concept of religious moderation in education is a form of internalization of religious moderation values, namely through the determination of educational policies and objectives, through curriculum formulation, and through the delivery of values hidden in the hidden curriculum. In schools, the values and attitudes of religious moderation are realized in classrooms that involve teachers as facilitators and students as subject learners